In Vitro Antileptospiral Activity of Trigona thoracia Propolis and its Synergistic Effects with Commonly Prescribed Antibiotics - Ismail, Siti Radziah; Ismail, Salwani; Deris, Zakuan Zainy; Ismail, Nabilah (IIUM Medical Journal Malaysia, 2020)
Introduction: Trigona thoracica propolis is known to have antimicrobial properties, however its antileptospiral properties and its synergistic effects with commonly prescribed antibiotics are scarcely documented. This study aimed to evaluate the antileptospiral properties of Trigona thoracica against pathogenic Leptospira species (spp.) and to study its synergistic effects with commonly prescribed antibiotics. Materials and Methods: The tested Leptospira serovars were Australis, Bataviae, Canicola and Javanica. Aqueous extract propolis (AEP) and ethanolic extracts propolis (EEP) were used. Broth dilution methods were used to determine the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and the synergistic effects between the propolis and the tested antibiotics. The synergistic effects was evaluated by using the fractional inhibitory concentration (FIC) index. Morphological changes of the treated Leptospira were observed under a Scanning Electron Microscope (SEM). Results: The AEP and EEP were found to have antileptospiral properties against the tested Leptospira spp. The synergy result showed that only combination of AEP and penicillin G against serovar Australis has demonstrated synergistic effect with the FIC index of 0.38. Morphological study using SEM showed significant structural changes of the treated Leptospira spp. Conclusions: The result suggests that Trigona thoracica propolis could potentially be used as either a complimentary or an alternative therapeutic agent against pathogenic Leptospira spp.